Flexible conductive carbon cloth and preparation method thereof
The conductive carbon cloth is solved by using acrylonitrile, preoxidation, carbonization and surfactivity treatments in the preparation of conductive carbon cloth, combined with the use of hydrophilic monomers and carbon nanotubes, and the hydrophilic modification of chitosan. The high production cost, insufficient hydrophilicity and electrochemical activity have been achieved to prepare high-performance conductive carbon cloth.
Patent Information
- Application Number
- CN202411805573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing conductive carbon cloth has high production costs, insufficient hydrophilicity and electrochemical activity, which affects its performance as an electrode material.
By using acrylonitrile as a raw material, polymerization, preoxidation, spinning weaving, carbonization and surface activation treatments were performed, combined with hydrophilic monomers added and composited with carbon nanotubes during the polymer synthesis stage, and finally chitosan was used for philology Modified by water, a conductive carbon cloth with high conductivity, hydrophilicity and electrochemical activity was prepared.
The high conductivity, high electrochemical activity, high hydrophilicity and mechanical properties of the conductive carbon cloth are achieved, reducing production costs and improving its performance as an electrode material.
Smart Images

Figure CN119465631A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and in particular relates to a flexible conductive carbon cloth and a preparation method thereof. Background Art
[0002] Conductive carbon cloth (CC) has the characteristics of large specific surface area, strong corrosion resistance and good flexibility, and can be widely used in the fields of medical, military, environmental protection, and new energy vehicles. During the preparation process, the surface area of the carbon fiber will expand sharply, and the surface will be grooved, which greatly enhances its ability to adsorb small particles and can become an excellent adsorption material for environmental protection filtration purposes; at the same time, the carbon material itself has a high friction coefficient and high thermal conductivity, and is also a natural friction material; because the conductive carbon fiber cloth itself is made at high temperature, its high temperature resistance can reach more than 1000℃, and it is also a good thermal insulation material.
[0003] However, due to poor hydrophilicity and few electrochemical reaction active sites, the commercial carbon cloth has a low specific capacity when directly used as an electrode material, which affects the electrode performance. The carbon cloth needs to be activated. According to patent literature reports, there are two commonly used activation methods. One is to use the carbon cloth directly as a flexible electrode material after being treated by some activation methods such as electrochemical activation and chemical redox activation, such as strong acid immersion corrosion, high-temperature heat treatment surface oxidation, etc.; the second method is to use the carbon cloth as a substrate and load other active substances on its surface, including nanometals, metal oxides, polymers and other carbon materials (new carbon nanomaterials such as carbon nanotubes and graphene). The interface resistivity of the conductive carbon cloth prepared after surface treatment is reduced and the electrocatalytic activity is improved, which shows that different surface treatment conditions can greatly affect the interface bonding performance of carbon fiber electrode materials, thereby affecting the conductive properties and electrochemical properties of electrode materials.
[0004] The above-mentioned conductive carbon cloth activation treatment methods such as high-temperature heat treatment methods require more energy consumption and place higher requirements on equipment such as high temperature resistance, corrosion resistance and air tightness, etc., which are costly and difficult to mass produce. Chemical treatment methods such as strong acid corrosion increase safety hazards, and their performance after treatment still does not meet the requirements of electrode materials. Therefore, it is necessary to improve the existing activation treatment methods, reduce the production cost of conductive carbon cloth, and improve its hydrophilicity and electrochemical activity. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention aims to provide a flexible conductive carbon cloth and a preparation method thereof. The prepared conductive carbon cloth has high conductivity, mechanical properties, flame retardancy, hydrophilicity, and electrochemical properties, which solves the defects of the existing conductive carbon cloth, such as high production cost, poor hydrophilicity, and poor electrochemical activity.
[0006] To achieve the above-mentioned purpose, the present invention provides a flexible conductive carbon cloth, which uses acrylonitrile as a raw material, obtains pre-oxidized silk through polymerization and pre-oxidation, activates the pre-oxidized silk, and performs spinning and weaving, and obtains the cloth after high-temperature carbonization and surface activation treatment; wherein hydrophilic monomers are added in the polymer synthesis stage, and hydrophilic groups are introduced into the polyacrylonitrile molecular chain to increase the affinity of the fiber to water; at the same time, the prepared pre-oxidized silk is compounded with carbon nanotubes, and carbonized in different temperature zones under an inert gas, so that the pre-oxidized silk and the carbon nanotubes produce a strong binding force, and at the same time, the specific surface area of the carbon cloth is increased, and the conductivity and softness are improved; finally, chitosan is used to perform hydrophilic treatment on the carbon cloth, and the chitosan molecules are grafted onto the surface of the pre-oxidized silk fibers through the reaction of the aldehyde groups on both sides of glutaraldehyde with the -NH2 on the pre-oxidized silk and chitosan. At the same time, the chitosan molecular chains react with each other and are coated on the surface of the pre-oxidized silk fibers, thereby improving the hydrophilicity of the carbon cloth.
[0007] Another aspect of the present invention provides a method for preparing a flexible conductive carbon cloth, comprising the following steps:
[0008] (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn;
[0009] (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers, and the short fibers are pulled through a highly oriented acidified carbon nanotube solution to make the acidified carbon nanotubes evenly adhere to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth;
[0010] (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace at a step temperature. The temperature in the furnace is controlled between 400°C and 1500°C, and the carbon cloth travel speed is between 0.4 and 0.6 m / min.
[0011] (4) Activation: The carbon cloth is immersed in an ethylenediamine solution and reacted for 15-30 minutes. After washing with an ethanol aqueous solution, the carbon cloth is placed in a chitosan mixed solution and continued to react for 2-4 hours. After washing and drying, the conductive carbon cloth is obtained.
[0012] Preferably, the polymerization reaction in step (1) comprises the following steps: copolymerizing ethylene glycol monovinyl ether and maleic anhydride at a molar ratio of 1:1 to obtain a crude copolymer; adding acrylonitrile, the crude copolymer and an initiator to an alcohol solution of dimethyl sulfoxide for polymerization to obtain a polyacrylonitrile stock solution. Hydrophilic copolymers of ethylene glycol monovinyl ether and maleic anhydride are used, and hydrophilic groups exist in the monomer structure. These groups have the ability to adsorb water molecules in the environment, thereby forming an extremely thin layer of water molecule film on the surface of the material. Under the action of the water molecule film, a large number of water molecules undergo ionization reactions to generate positive and negative ions, which effectively improves the surface conductivity and hydrophilicity.
[0013] Preferably, the mass ratio of acrylonitrile to crude copolymer is 95-98:2-5, preferably 96% by mass of acrylonitrile and 4% by mass of crude copolymer.
[0014] Preferably, the initiator is benzoyl peroxide-N,N-diethylaniline.
[0015] Preferably, the mass percentage of dimethyl sulfoxide in the alcohol solution of dimethyl sulfoxide is 40-50%, and the alcohol is any one of ethanol and propanol.
[0016] Preferably, the short fibers in step (2) are 4-10 cm long, the pre-oxidized silk yarn has a yarn count of 21, and the weaving is carried out in a three-dimensional weaving manner to form a plain woven fabric.
[0017] Preferably, the mass concentration of the acidified carbon nanotube solution in step (2) is 1-3 g / L, the acidified carbon nanotubes are obtained by ultrasonically treating carbon nanotubes in a concentrated sulfuric acid solution, and the acidified carbon nanotube solution is obtained by dispersing and dissolving the acidified carbon nanotubes in ethanol.
[0018] Preferably, the continuous carbonization furnace in step (3) is divided into a low temperature zone of 400-600°C, a medium temperature zone of 600-1000°C, and a high temperature zone of 1000-1500°C, each temperature zone stays for 2-3 minutes, and the protective gas is nitrogen or argon.
[0019] Preferably, the ethylenediamine solution in step (4) is a 20% ethylenediamine solution prepared by dissolving ethylenediamine in ethylene dichloride solution.
[0020] Preferably, the chitosan mixed solution in step (4) is composed of chitosan, acetic acid mixed solution and glutaraldehyde.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention uses acrylonitrile as a raw material, obtains pre-oxidized silk by polymerization and pre-oxidation, activates the pre-oxidized silk and performs spinning and weaving, and obtains a conductive carbon cloth after high-temperature carbonization and surface activation treatment. The conductive carbon cloth has high conductivity, high electrochemical activity, high hydrophilicity, mechanical properties and flame retardancy.
[0023] (2) The present invention increases the affinity of the fiber for water by adding hydrophilic monomers during the polymer synthesis stage and introducing hydrophilic groups into the polyacrylonitrile molecular chain; at the same time, the prepared pre-oxidized fibers are compounded with carbon nanotubes and carbonized in different temperature zones under an inert gas, so that the pre-oxidized fibers and the carbon nanotubes have a strong binding force, thereby increasing the specific surface area of the carbon cloth and improving the conductivity and softness.
[0024] (3) The present invention uses chitosan to perform hydrophilic modification on carbon cloth, so that the modified conductive carbon cloth has better hydrophilicity. There is a certain correlation between resistivity and hydrophilicity. Improving hydrophilicity can reduce the surface resistance of the conductive carbon cloth. Its resistivity is ≤3Ω·mm, which is lower than the resistivity of carbon cloth currently used in the market.
[0025] (4) The electrothermal conversion rate of the conductive carbon cloth prepared by the present invention reaches 98%, and the thickness is relatively thin, generally 0.3-1 mm. The modification of carbon nanotubes and chitosan improves the conductivity of the conductive carbon cloth and increases the capacity of the conductive carbon cloth. When used as an electrode material for energy storage batteries, it can increase the energy density of the battery and reduce the volume of the battery, reduce the liquid flow resistance of the electrode in the battery, and improve the charge and discharge efficiency of the battery.
[0026] (5) The carbon cloth prepared by the present invention has all the functions of non-combustible fabrics and can be widely used in electric heating therapy, household floor heating, wall heating, electric heating products, pipeline insulation, electromagnetic shielding, shielding and anti-detection of military combat tents, sewage treatment, air purification, chemical and gas masks, ultra-large capacity capacitors, etc. It is particularly suitable as an electrode material for liquid flow energy storage batteries and has unlimited application development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 is a scanning electron microscope image of the conductive carbon cloth prepared in Comparative Example 6 of the present invention;
[0029] Figure 2 This is a scanning electron microscope image of the conductive carbon cloth prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0031] A method for preparing a flexible conductive carbon cloth comprises the following steps:
[0032] (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn;
[0033] (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers, and the short fibers are pulled through a highly oriented acidified carbon nanotube solution to make the acidified carbon nanotubes evenly adhere to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth;
[0034] (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace at a step temperature. The temperature in the furnace is controlled between 400°C and 1500°C, and the carbon cloth travel speed is between 0.4 and 0.6 m / min.
[0035] (4) Activation: The carbon cloth is immersed in an ethylenediamine solution and reacted for 15-30 minutes. After washing with an ethanol aqueous solution, the carbon cloth is placed in a chitosan mixed solution and continued to react for 2-4 hours. After washing and drying, the conductive carbon cloth is obtained.
[0036] It should be noted that the specific process flow of preparing the polyacrylonitrile pre-oxidized yarn in step (1) is as follows:
[0037] 1) preparing polyacrylonitrile spinning solution: copolymerizing ethylene glycol monovinyl ether and maleic anhydride at a molar ratio of 1:1 to obtain a crude copolymer; adding 96 parts of acrylonitrile, 4 parts of the crude copolymer and 20 parts of an initiator to an alcohol solution of 380 parts of dimethyl sulfoxide, heating the mixture to 75°C for reaction for 1 hour, then heating the mixture to a second stage of 95°C at a heating rate of 0.2°C / min for reaction for 2 hours to obtain a polyacrylonitrile polymer, and then filtering and removing the monomers to obtain a polyacrylonitrile spinning solution;
[0038] 2) preparing polyacrylonitrile precursor: extruding the polyacrylonitrile spinning solution from the spinneret through negative pressure degassing, obtaining polyacrylonitrile primary fibers by wet spinning, removing the solvent with salt water, and performing two-stage hot water drawing, wherein the first stage hot water temperature is 63° C., and the drawing ratio is 1.5 times; the second stage hot water temperature is 92° C., and the drawing ratio is 1.7 times; after hot water drawing, the washed silk is air-dried and then oiled, and after drying, steam drawing is performed, the steam pressure is 0.48 MPa, and the drawing ratio is 5 times, to obtain the polyacrylonitrile precursor;
[0039] 3) Preparation of pre-oxidized yarn: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace to 200°C at a rate of 3°C / min in an air atmosphere, keep it warm for 15 minutes, then raise the temperature to 260°C at a rate of 2°C / min, keep it warm for 30 minutes, and naturally cool to room temperature to obtain pre-oxidized yarn 1#.
[0040] It should be noted that the specific process flow of preparing the polyacrylonitrile pre-oxidized yarn in step (1) is as follows:
[0041] 1) preparing polyacrylonitrile spinning solution: copolymerizing ethylene glycol monovinyl ether and maleic anhydride at a molar ratio of 1:1 to obtain a crude copolymer; adding 95 parts of acrylonitrile, 5 parts of the crude copolymer and 20 parts of an initiator to an alcohol solution of 380 parts of dimethyl sulfoxide, heating the mixture to 75° C. for reaction for 1 hour, then heating the mixture to a second stage of 95° C. at a heating rate of 0.2° C. / min for reaction for 2 hours to obtain a polyacrylonitrile polymer, and then filtering and removing the monomers to obtain a polyacrylonitrile spinning solution;
[0042] 2) preparing polyacrylonitrile precursor: extruding the polyacrylonitrile spinning solution from the spinneret through negative pressure degassing, obtaining polyacrylonitrile primary fibers by wet spinning, removing the solvent with salt water, and performing two-stage hot water drawing, wherein the first stage hot water temperature is 63° C., and the drawing ratio is 1.5 times; the second stage hot water temperature is 92° C., and the drawing ratio is 1.7 times; after hot water drawing, the washed silk is air-dried and then oiled, and after drying, steam drawing is performed, the steam pressure is 0.48 MPa, and the drawing ratio is 5 times, to obtain the polyacrylonitrile precursor;
[0043] 3) Preparation of pre-oxidized yarn: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace to 200°C at a rate of 3°C / min in an air atmosphere, keep it warm for 15 minutes, then raise the temperature to 260°C at a rate of 2°C / min, keep it warm for 30 minutes, and naturally cool to room temperature to obtain pre-oxidized yarn 2#.
[0044] It should be noted that the specific process flow of preparing the polyacrylonitrile pre-oxidized yarn in step (1) is as follows:
[0045] 1) preparing polyacrylonitrile spinning solution: copolymerizing ethylene glycol monovinyl ether and maleic anhydride at a molar ratio of 1:1 to obtain a crude copolymer; adding 98 parts of acrylonitrile, 2 parts of the crude copolymer and 20 parts of an initiator to an alcohol solution of 380 parts of dimethyl sulfoxide, heating the mixture to 75°C for reaction for 1 hour, then heating the mixture to a second stage of 95°C at a heating rate of 0.2°C / min for reaction for 2 hours to obtain a polyacrylonitrile polymer, and then filtering and removing the monomers to obtain a polyacrylonitrile spinning solution;
[0046] 2) preparing polyacrylonitrile precursor: extruding the polyacrylonitrile spinning solution from the spinneret through negative pressure degassing, obtaining polyacrylonitrile primary fibers by wet spinning, removing the solvent with salt water, and performing two-stage hot water drawing, wherein the first stage hot water temperature is 63° C., and the drawing ratio is 1.5 times; the second stage hot water temperature is 92° C., and the drawing ratio is 1.7 times; after hot water drawing, the washed silk is air-dried and then oiled, and after drying, steam drawing is performed, the steam pressure is 0.48 MPa, and the drawing ratio is 5 times, to obtain the polyacrylonitrile precursor;
[0047] 3) Preparation of pre-oxidized yarn: Place the above-mentioned polyacrylonitrile precursor into an oxidation furnace, raise the temperature in the furnace to 200°C at a rate of 3°C / min in an air atmosphere, keep it warm for 15 minutes, then raise the temperature to 260°C at a rate of 2°C / min, keep it warm for 30 minutes, and naturally cool to room temperature to obtain pre-oxidized yarn 3#.
[0048] It should be noted that step (2) spinning and weaving comprises the following steps:
[0049] 1) The pre-oxidized yarn after pretreatment is successively subjected to cleaning, carding and drawing, and 5-6 yarns are drawn into one thick strip. After drawing, the weight of the strip is between 150-300g / m;
[0050] 2) The wool tops after drawing are put into the spinning machine for twisting into roving, the twist of the yarn is 130 twists, the yarn count is 12-15 yarns, and after the roving is twisted, the spun yarn is twisted, the twist of the yarn is 250-350 twists, the yarn count is 21 yarns, and after the yarn is spun, a 3-ply process is performed to synthesize 21 / 3 yarns;
[0051] 3) After the finished yarn is wound on a bobbin, it is put on a precision loom for weaving. The weaving style is plain weave, with a warp density of 108 strands / 10cm and a weft density of 102 strands / 10cm. The overall grey cloth weight is 320±5g / ㎡, and the cloth batch width is 80±5mm wide.
[0052] It should be noted that the mass concentration of the acidified carbon nanotube solution in step (2) is 1-3 g / L, and the acidified carbon nanotube solution is prepared by the following method: ultrasonically treating the carbon nanotubes in a concentrated sulfuric acid solution, washing until the solution is neutral and then drying, dispersing and dissolving the dried acidified carbon nanotubes in an ethanol solution to prepare a 1-3 g / L acidified carbon nanotube solution.
[0053] Example 1
[0054] A method for preparing a flexible conductive carbon cloth comprises the following steps:
[0055] (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn 1#;
[0056] (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers of 4-10 cm, and the short fibers are pulled through a highly oriented 1 g / L acidified carbon nanotube solution to make the acidified carbon nanotubes evenly attached to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth;
[0057] (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace under a nitrogen atmosphere with a step temperature. The temperature in the furnace is controlled between 400°C and 1500°C, with a low temperature zone of 400°C, a medium temperature zone of 600°C, and a high temperature zone of 1000°C. Each temperature zone stays for 2 minutes, and the carbon cloth travels at a speed of 0.4 m / min.
[0058] (4) Activation: The carbon cloth is immersed in a 20% ethylenediamine solution for reaction for 15 minutes, washed with an ethanol aqueous solution, and then immersed in a chitosan mixed solution for further reaction for 2 hours. After washing and drying, a conductive carbon cloth is obtained; wherein the chitosan mixed solution is composed of chitosan, glutaraldehyde, and 20% acetic acid solution. 1 part by weight of glutaraldehyde is dissolved in 100 parts by weight of acetic acid mixed solution and stirred for 10 minutes, and 1 part by weight of chitosan is added and stirred for 15 minutes to obtain a chitosan mixed solution.
[0059] Example 2
[0060] A method for preparing a flexible conductive carbon cloth comprises the following steps:
[0061] (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn 2#;
[0062] (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers of 4-10 cm, and the short fibers are pulled through a highly oriented 2 g / L acidified carbon nanotube solution to make the acidified carbon nanotubes evenly attached to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth;
[0063] (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace under a nitrogen atmosphere at a step temperature. The temperature in the furnace is controlled between 400°C and 1500°C, with a low temperature zone of 600°C, a medium temperature zone of 1000°C, and a high temperature zone of 1500°C. Each temperature zone stays for 3 minutes, and the carbon cloth travels at a speed of 0.5 m / min.
[0064] (4) Activation: The carbon cloth is immersed in a 20% ethylenediamine solution for reaction for 20 minutes, washed with an ethanol aqueous solution, and then immersed in a chitosan mixed solution for further reaction for 3 hours. After washing and drying, a conductive carbon cloth is obtained; wherein the chitosan mixed solution is composed of chitosan, glutaraldehyde, and 20% acetic acid solution. 1 part by weight of glutaraldehyde is dissolved in 100 parts by weight of acetic acid mixed solution and stirred for 5 minutes, and 1 part by weight of chitosan is added and stirred for 20 minutes to obtain a chitosan mixed solution.
[0065] Example 3
[0066] A method for preparing a flexible conductive carbon cloth comprises the following steps:
[0067] (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn 3#;
[0068] (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers of 4-10 cm, and the short fibers are pulled through a highly oriented 3 g / L acidified carbon nanotube solution to make the acidified carbon nanotubes evenly attached to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth;
[0069] (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace under a nitrogen atmosphere at a step temperature. The temperature in the furnace is controlled between 400°C and 1500°C, with a low temperature zone of 500°C, a medium temperature zone of 800°C, and a high temperature zone of 1200°C. Each temperature zone stays for 2 minutes, and the carbon cloth travel speed is between 0.6 m / min.
[0070] (4) Activation: The carbon cloth is immersed in a 20% ethylenediamine solution for reaction for 30 minutes, washed with an ethanol aqueous solution, and then immersed in a chitosan mixed solution for further reaction for 4 hours. After washing and drying, a conductive carbon cloth is obtained; wherein the chitosan mixed solution is composed of chitosan, glutaraldehyde, and 20% acetic acid solution. 1 part by weight of glutaraldehyde is dissolved in 100 parts by weight of acetic acid mixed solution and stirred for 10 minutes, and 1 part by weight of chitosan is added and stirred for 10 minutes to obtain a chitosan mixed solution.
[0071] Example 4
[0072] A method for preparing a flexible conductive carbon cloth comprises the following steps:
[0073] (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn 1#;
[0074] (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers of 4-10 cm, and the short fibers are pulled through a highly oriented 2 g / L acidified carbon nanotube solution to make the acidified carbon nanotubes evenly attached to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth;
[0075] (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace under a nitrogen atmosphere at a step temperature. The temperature in the furnace is controlled between 400°C and 1500°C, with a low temperature zone of 550°C, a medium temperature zone of 950°C, and a high temperature zone of 1350°C. Each temperature zone stays for 2 minutes, and the carbon cloth travel speed is between 0.5 m / min.
[0076] (4) Activation: The carbon cloth was immersed in a 20% ethylenediamine solution for reaction for 20 minutes, washed with an ethanol aqueous solution, and then immersed in a chitosan mixed solution for further reaction for 3 hours. After washing and drying, a conductive carbon cloth was obtained; wherein the chitosan mixed solution consisted of chitosan, glutaraldehyde, and 20% acetic acid solution. 1 part by weight of glutaraldehyde was dissolved in 100 parts by weight of the acetic acid mixed solution and stirred for 8 minutes. 1 part by weight of chitosan was added and stirred for 15 minutes to obtain a chitosan mixed solution.
[0077] Comparative Example 1
[0078] Compared with Example 4, in step (1), ethylene glycol monovinyl ether and maleic anhydride are not added during the pre-oxidation process, and only acrylonitrile is used for copolymerization to obtain polyacrylonitrile pre-oxidized filaments. The remaining method steps are consistent with the method steps in Example 4 to prepare a conductive carbon cloth.
[0079] Comparative Example 2
[0080] Compared with Example 4, in step (2), the short fibers are not treated with acidified carbon nanotubes, and the polyacrylonitrile preoxidized fibers are directly spun and woven to obtain preoxidized fiber cloth. The remaining method steps are consistent with those in Example 4 to prepare a conductive carbon cloth.
[0081] Comparative Example 3
[0082] Compared with Example 4, step (4) activation treatment is omitted, and the remaining method steps are consistent with the method steps in Example 4 to prepare a conductive carbon cloth.
[0083] Comparative Example 4
[0084] Compared with Example 4, in step (1), ethylene glycol monovinyl ether and maleic anhydride are not added during the pre-oxidation process, and only acrylonitrile is used for copolymerization to obtain polyacrylonitrile pre-oxidized yarn; in step (2), the short fibers are not treated with acidified carbon nanotubes, and the polyacrylonitrile pre-oxidized yarn is directly spun and woven to obtain pre-oxidized yarn cloth. The remaining method steps are consistent with the method steps in Example 4 to prepare a conductive carbon cloth.
[0085] Comparative Example 5
[0086] Compared with Example 4, ethylene glycol monovinyl ether and maleic anhydride are not added during the pre-oxidation process in step (1), and only acrylonitrile is used for copolymerization to obtain polyacrylonitrile pre-oxidized filaments; step (4) activation treatment is omitted, and the remaining method steps are consistent with the method steps in Example 4 to prepare a conductive carbon cloth.
[0087] Comparative Example 6
[0088] Compared with Example 4, in step (2), the short fibers are not treated with acidified carbon nanotubes, and the polyacrylonitrile pre-oxidized fibers are directly spun and woven to obtain pre-oxidized fiber cloth. The activation treatment in step (4) is omitted, and the remaining method steps are consistent with those in Example 4 to prepare a conductive carbon cloth.
[0089] Comparative Example 7
[0090] Compared with Example 4, ethylene glycol monovinyl ether and maleic anhydride are not added during the pre-oxidation process in step (1), only acrylonitrile is used for copolymerization to obtain polyacrylonitrile pre-oxidized fibers, and the short fibers in step (2) are not treated with acidified carbon nanotubes. The polyacrylonitrile pre-oxidized fibers are directly spun and woven to obtain pre-oxidized fiber cloth, and the activation treatment in step (4) is omitted. The remaining method steps are consistent with the method steps in Example 4 to prepare a conductive carbon cloth.
[0091] Experimental analysis
[0092] In order to further prove the technical effect of the flexible conductive carbon cloth prepared by the technical solution disclosed in the present invention, the inventors conducted a performance measurement experiment on the performance of the conductive carbon cloth prepared by the present invention. The specific experimental contents are as follows, and the specific experimental test results are shown in Table 1:
[0093] 1. Micromorphology: The conductive carbon cloth was cut into 2 cm × 2 cm samples and glued to the sample stage. After gold spraying, the micromorphology of the fiber was observed under a scanning electron microscope.
[0094] 2. Carbon content test: Use 1400℃ high temperature carbonization and original thickness of 0.8mm cloth for testing, and use TG combustion weight loss method to measure the carbon content of the sample;
[0095] 3. Resistivity test: Use a multimeter to test the resistance of the sample at a distance of 10 cm;
[0096] 4. Porosity test: The porosity is measured by mercury intrusion method;
[0097] 5. Hydrophilicity test: The hydrophilicity of the carbon cloth is determined by the water contact angle. The Krüss DSA 30 contact angle tester is used for the contact angle test. Distilled water is used as the droplet. The smaller the contact angle, the better the hydrophilicity.
[0098] from Figure 1-2 It can be seen that the internal fiber surface of the carbon cloth of the present invention changes before and after the activation treatment modification. Before the activation modification, the fiber surface is smooth. After the hydrophilic modification of the acidified carbon nanotubes and chitosan, the fiber presents a relatively rough surface, which indicates that the fiber surface is coated with the acidified carbon nanotubes and chitosan, indicating that the hydrophilic modification of the conductive carbon cloth prepared by the method of the present invention is successful.
[0099] The test results in Table 1 further prove that the conductive carbon cloth prepared by the present invention has excellent electrical conductivity and hydrophilicity. It can be seen from the data of the examples and comparative examples in the table that the resistivity of the conductive carbon cloth has a certain correlation with the hydrophilicity. The hydrophilic molecule chitosan is introduced into the hydrophilic modified conductive carbon cloth, and there are a large number of hydrophilic groups -OH on its molecular chain, which helps the transmission of hydroxide ions in the electrolyte and reduces the resistance of ion transfer during electrolysis. Therefore, the modified conductive carbon cloth shows a lower resistivity (see the test data of Example 4 and Comparative Example 3). On the other hand, the thickness of the conductive carbon cloth is also an important factor affecting the resistivity. Generally speaking, the greater the thickness of the conductive carbon cloth, the longer the distance that the ions pass during the electrolysis process, and the greater the resistivity of the conductive carbon cloth. The average thickness of the conductive carbon cloth prepared by the present invention is about 0.6 mm, and the ion passing distance is short, so the resistivity is low. It can be seen from the contact angle test results that the present invention increases the affinity of the fiber for water by adding hydrophilic monomers in the polymer synthesis stage, thereby introducing hydrophilic groups into the polyacrylonitrile molecular chain, thereby improving the hydrophilicity of the conductive carbon cloth (see the test results of Example 4 and Comparative Examples 1 and 4); chitosan is used to further hydrophilically modify the carbon cloth, so that the modified conductive carbon cloth has better hydrophilicity (see Example 4 and Comparative Examples 3 and 6).
[0100] Table 1 Performance test results of flexible conductive carbon cloth
[0101] project Thickness / mm Carbon content / % Resistivity / Ω·mm Porosity Contact angle Example 1 0.6 99.4 3.2 79.8 55° Example 2 0.6 99.7 2.8 82.1 57° Example 3 0.6 99.5 3.1 81.5 56° Example 4 0.6 99.5 2.6 83.3 53° Comparative Example 1 0.6 98.5 3.4 82.4 62° Comparative Example 2 0.6 99.1 3.6 76.8 61° Comparative Example 3 0.6 99.3 3.8 81.7 79° Comparative Example 4 0.6 98.9 4.2 74.9 62° Comparative Example 5 0.6 99.1 4.2 80.5 83° Comparative Example 6 0.6 98.9 4.1 74.3 82° Comparative Example 7 0.6 99.2 5.3 69.8 87°
[0102] At the same time, the inventors also tested the electrochemical performance of the conductive carbon cloth. The conductive carbon cloths prepared in the embodiment and the comparative example were respectively installed on the positive electrode liquid flow plate of the vanadium liquid flow battery to assemble the vanadium liquid flow battery. 2 The rate performance of a single cell is tested at a current density of, that is, the voltage efficiency, coulomb efficiency, and energy efficiency are tested. From the data in Table 2, it can be seen that compared with comparative examples 5-7, the conductive carbon cloth prepared in Examples 1-4 of the present invention has higher voltage efficiency and energy efficiency. This is because the conductive carbon cloth prepared by the method of the present invention has a porous structure, which increases the specific surface area of the carbon cloth and provides more reaction sites for the vanadium ion reaction; the carbon fiber of the present invention is also loaded with acidified carbon nanotubes and chitosan, which can enhance the catalytic activity and hydrophilicity of the carbon cloth. The carbon nanotubes have good electrical conductivity, which can effectively improve the electrical conductivity of the carbon cloth, reduce the charge transfer resistance, reduce the activation polarization and mass transfer polarization inside the battery, and improve the voltage efficiency and energy efficiency of the battery.
[0103] Table 2 Electrochemical performance test of different flexible conductive carbon cloths
[0104] Voltage efficiency / % Coulomb efficiency / % Energy efficiency / % Example 1 90.5 97.8 86.9 Example 2 91.2 97.8 87.4 Example 3 90.7 97.6 87.2 Example 4 91.4 98.1 87.6 Comparative Example 1 88.9 97.6 85.6 Comparative Example 2 82.3 97.7 79.2 Comparative Example 3 79.6 97.5 77.4 Comparative Example 4 71.8 97.4 68.8 Comparative Example 5 72.3 97.5 69.4 Comparative Example 6 75.4 97.3 71.9 Comparative Example 7 67.2 97.1 65.3
[0105] In summary, the conductive carbon cloth prepared by the present invention uses acrylonitrile as raw material, obtains pre-oxidized silk through polymerization and pre-oxidation, activates the pre-oxidized silk and performs spinning and weaving, and obtains the conductive carbon cloth after high-temperature carbonization and surface activation treatment. The conductive carbon cloth has high conductivity, high electrochemical activity, high hydrophilicity, mechanical properties and flame retardancy, so as to improve the disadvantages of low capacitance and low rate characteristics caused by poor hydrophilicity and low conductivity of existing carbon cloth. The prepared conductive carbon cloth is not easy to expand or collapse during long-term charging and discharging, thereby increasing the stability of the conductive carbon cloth as an electrode material.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.
Claims
1. A method for preparing a flexible conductive carbon cloth, characterized in that: The following steps are involved: (1) Pre-oxidation: acrylonitrile, ethylene glycol monovinyl ether, maleic anhydride and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized, defoamed and spun to obtain polyacrylonitrile precursor; the precursor is subjected to pre-oxidation treatment to obtain polyacrylonitrile pre-oxidized yarn; (2) Weaving: The polypropylene pre-oxidized yarn is stretched and broken to obtain short fibers, and the short fibers are pulled through a highly oriented acidified carbon nanotube solution to make the acidified carbon nanotubes evenly adhere to the pre-oxidized yarn. After drying, the obtained pre-oxidized yarn is spun and woven to obtain pre-oxidized yarn cloth; (3) Carbonization: The pre-oxidized silk cloth is carbonized in a continuous carbonization furnace at a step temperature to obtain a carbon cloth. The temperature in the furnace is controlled between 400°C and 1500°C, and the carbon cloth travel speed is between 0.4 and 0.6 m / min. (4) Activation: The carbon cloth is immersed in an ethylenediamine solution and reacted for 15-30 minutes. After washing with an ethanol aqueous solution, the carbon cloth is placed in a chitosan mixed solution and continued to react for 2-4 hours. After washing and drying, the conductive carbon cloth is obtained.
2. The method for preparing the flexible conductive carbon cloth according to claim 1, characterized in that: The polymerization reaction in step (1) comprises the following steps: copolymerizing ethylene glycol monovinyl ether and maleic anhydride at a molar ratio of 1:1 to obtain a crude copolymer; and adding acrylonitrile, the crude copolymer and an initiator to an alcohol solution of dimethyl sulfoxide to carry out a polymerization reaction to obtain a polyacrylonitrile stock solution.
3. The method for preparing the flexible conductive carbon cloth according to claim 2, characterized in that: The mass ratio of acrylonitrile to crude copolymer is 95-98:2-5.
4. The method for preparing the flexible conductive carbon cloth according to claim 2, characterized in that: The mass percentage of dimethyl sulfoxide in the alcohol solution of dimethyl sulfoxide is 40-50%, and the alcohol is any one of ethanol and propanol.
5. The method for preparing the flexible conductive carbon cloth according to claim 1, characterized in that: In step (2), the short fibers are 4-10 cm long, the pre-oxidized silk yarn is 21-count, and the weaving spinning is carried out in a three-dimensional weaving manner.
6. The method for preparing the flexible conductive carbon cloth according to claim 1, characterized in that: The continuous carbonization furnace in step (3) is divided into a low temperature zone of 400-600°C, a medium temperature zone of 600-1000°C, and a high temperature zone of 1000-1500°C. Each temperature zone stays for 2-3 minutes, and the protective gas is nitrogen or argon.
7. The method for preparing the flexible conductive carbon cloth according to claim 1, characterized in that: The ethylenediamine solution in step (4) is a 20% ethylenediamine solution prepared by dissolving ethylenediamine in ethylene dichloride solution.
8. The method for preparing the flexible conductive carbon cloth according to claim 1, characterized in that: The chitosan mixed solution in step (4) is composed of chitosan, acetic acid mixed solution and glutaraldehyde.
9. A flexible conductive carbon cloth prepared by the preparation method according to claims 1-8.
Citation Information
Cited By
Activating and carbonizing method of polyacrylonitrile pre-oxidized yarn and carbon fiber
CN121951745A
Method for activating and carbonizing polyacrylonitrile pre-oxidized filaments and carbon fibers
CN121951745B